126k views
4 votes
The work of a student to solve the equation 4(2x − 4) = 8 + 2x + 8 is shown below: Step 1: 4(2x − 4) = 8 + 2x + 8

Step 2: 6x − 8 = 16 + 2x
Step 3: 6x − 2x = 16 + 8
Step 4: 4x = 24
Step 5: x = 6
In which step did the student first make an error and what is the correct step? Group of answer choices
Step 2; 8x − 4 = 2(6 + x + 6)
Step 2; 8x − 16 = 16 + 2x Step 3; 6x − 2x = 16 − 8
Step 3; 6x + 2x = 16 + 8

1 Answer

4 votes

Answer: step 3 is incorrect. the student should have added 8 to 16 and subtracted 2x from 6x.

User Bhargav Patel
by
5.8k points